Extracellular histones reduce survival and angiogenic responses of late outgrowth progenitor and mature endothelial cells - Mena, Hebe Agustina (2016)
Extracellular histones are highly augmented in sites of neovessel formation, such as regeneration tissues. We studied histone effect on survival and angiogenic activity of mature and progenitor endothelial cells. Extracellular histones trigger apoptosis and pyroptosis and reduce angiogenesis in vivo and in vitro. Histone blockade can be useful as a therapeutic strategy to improve angiogenesis and tissue regeneration.